The Risk Factors for Exposure to Covid-19 in Diabetes Patients in the Johar Baru Health Centre Work Area - Dewi Prabawati; Yovita Setiyowati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: The study aims to analyse the risk factors for exposure to Covid-19 in Diabetes Mellitus (DM) Patients in the Johar Baru Health Centre work area. Design: This research was an observational analytic with a cross-sectional design. 146 DM patients were selected using the purposive sampling technique as respondents. Four instruments were employed in this study, they were The Perceived Stress Scale, modified Diabetes Self-management Questionnaire, Self-assessment form from the Ministry of Health to measure the risk of exposure to Covid-19, and The Covid-19 Preventive Behaviour Questionnaire, which was compiled based on a literature study and tested for validity and reliability. Methods: This research is a quantitative descriptive research. Results : Using Kendal's Tau B statistics, the risk of being exposed to Covid-19 was found to have a significant relationship to the length of suffering from DM, comorbidities, stress levels, self-management, and Covid-19 preventive behaviour with a p-value <0.05. The multiple linear regression test found that the risk of being exposed to Covid-19 was influenced by the variable duration of suffering from DM, stress level, and Covid preventive behaviour (p-value < 0.05) with the results of Cox and Snell R = 0.382 indicating that the independent variable contributes 38.2%. Conclusions: DM patients were in high risk for exposure Covid 19, thus they need to control stress levels and carry out Covid preventive behaviour by prioritizing optimal health procedures to prevent the risk of being exposed to Covid-19.